ZnO/PVP nanoparticles induce gelation in type I collagen. (February 2016) - Lian, Jiaxin; Agban, Yosra; Cheong, Soshan; Kuchel, Rhiannon P.; Raudsepp, Allan; Williams, Martin A.K.; Rupenthal, Ilva D.; Henning, Anna; Tilley, Richard D.; Holmes, Geoff; Prabakar, Sujay
Graphical abstract: Highlights: ZnO/PVP NPs can induce gelation in type I collagen without the need for external cross-linkers. The ZnO/PVP collagen hydrogels showed enhanced mechanical and thermal properties. The ZnO/PVP collagen hydrogels exhibited low cytotoxicity to human corneal epithelial cells. Abstract: Collagen based hydrogels have similar properties to native cornea and play an important role in ocular drug delivery. Here we report the preparation of zinc oxide nanoparticle/collagen hydrogels (collagen ZnO/PVP) without the need of an external cross-linking agent. The resulting hydrogels had sufficient mechanical strength to be manipulated and transferred without damaging its structure. Differential scanning calorimetry showed an increase in the denaturation temperature on increasing the ZnO/PVP NPs ratio. Whilst rheological measurements of the collagen hydrogels suggest that strong hydrogels were formed, at high concentration of ZnO/PVP NPs a decrease in G ′ can be observed. The responses of retinal epithelial cells (ARPE-19) to the collagen ZnO/PVP hydrogels were examined by cell viability assays and exhibited minimal cytotoxicity. The collagen ZnO/PVP hydrogel might be an excellent candidate for ocular drug delivery applications.